Utlendinger i Norge. Norsk innvandringpolitikk, grunner til og følger av migrasjonen (2008) - Lewandowska, Katarzyna (Folia Scandinavica Posnaniensia, 2009)
The aim of the article is to describe the present situation regarding immigrants in Norway. Most of the data that I am using with respect to this matter comes from Internet resources, as most of the statistics are available online only. The moment that can be regarded as crucial for immigrant history in Norway is the late 60ties of the 20th century. Guest workers from Pakistan came to the country invited by the Norwegian government. In 1975 the so-called ‘innvandringsstop’ (immigration-stop) regulation was introduced to prevent flooding the country with incoming foreigners. The statistics show that no such significant migration was observed again until 2007–2008 when Polish workers began to come to Norway in large groups. Presently, the largest immigrant groups in Norway are Poles, Pakistani, Germans and Iraqi. There are four important reasons for migration: economic, family, political (refugees) and educational. Work and family are definitely the most common ones. The law concerning immigration was established in 1988 and it is called ‘Utlendingsforskriften’. Moreover, the Norwegian immigration policy respects all the laws and regulations in force in all the EU countries and that apply to the members of the United Nations organization. Nowadays, the Norwegian government is working on a new immigration law that is planned to be introduced in 2010.